Persepsi Pemustaka Terhadap Kompetensi Pustakawan Dalam Pemenuhan Kebutuhan Informasi Di Perpustakaan Institut Teknologi Padang - Mufrizah, Hasnul Mardiah; Ardoni, Ardoni (Scinary, 2024)
This research aims to describe librarians' perceptions of the competence of librarians at the Padang Institute of Technology library based on four indicators: knowledge, understanding, skills, attitudes, values, interests and motivation. The type of research used in this research is quantitative with descriptive methods. This research involved 311 respondents, namely 73 student respondents from the class of 2019, 78 respondents from the class of 2020, 80 respondents from the class of 2021, and 80 respondents from the class of 2022 who were selected through proportionate stratified random sampling. from a population of 1430 users. The variable in this research is librarian competency. Based on the data analysis carried out, it shows that there is a user perception of librarian competence with seven indicators with an average of 2.57 in the good/high category.